Guide to Evidence-Based Physical Therapist Practice - Jewell Dianne V (Jones And Bartlett Learning, 2018)
This book teaches the knowledge and skills to evaluate medical evidence and apply it to the practice of physical therapy. Preface, Acknowledgements, Principles of Evidence-Based Physical Therapist Practice, Evidence-Based Physical Therapist Practice, What is Evidence?, The Quest for Evidence: Getting Started, Elements of Evidence, Questions and Theories and Hypotheses, Research Design, Research Subjects, Variables and Their Measurement, Validity in Research Findings, Unraveling Statistical Mysteries: Description, Unraveling Statistical Mysteries: Inference, Appraising the Evidence, Appraising Evidence about Diagnostic Tests and Clinical Measures, Appraising Evidence about prognostic (Risk) Factors, Appraising Evidence about Interventions, Appraising Evidence about Clinical Prediction Rules, Appraising Outcomes Research, Appraising Evidence about Self-Report Outcomes Measures, Appraising Collections of Evidence: Systematic Reviews, Appraising Collections of Evidence: Clinical Practice Guidelines, Appraising Qualitative Research Studies, Evidence in Practice, Patient or Client Preferences and Values, Index